The Development of Community Spirituality through the Assembly of Shalawat - Fauziah, Hasnah; Anam, Khoirul (Khatulistiwa, 2021)
The spiritual condition of today’s society, where they tend to feel tired in facing the crush of problems in globalization era. One effort to overcome the problem is to follow the activities of society, such as Shalawat Nariyah. By following the assembly of shalawat nariyah, people can develop their spirituality, so that they will be easier to deal with every problem. The results of this study indicates that by following the assembly shalawat nariyah, spirituality of Jatilengger villagers increased. This is seen from the development process based on ice block theory. Many parties who play a role in the development ranging from Kyai who play a direct role and motivate the jama'ah, then the existence of the chairman of jama'ah who always try to make his jama'ah always istiqomah, until the existence of donors who are very meritorious in arousing the jamaah. In fact all members of jamaah also have an interrelated role.